A community-based multilevel intervention for smoking, physical activity and diet: short-term findings from the Community Interventions for Health programme in Hangzhou, China. Issue 4 (2nd December 2013) - Lv, Jun; Liu, Qing-Min; Ren, Yan-Jun; He, Ping-Ping; Wang, Sheng-Feng; Gao, Fang; Li, Li-Ming; ,
Abstract : Background: To assess the short-term impact of a comprehensive, community-based multilevel intervention on knowledge, beliefs and practices with respect to smoking, physical activity and diet in Hangzhou, China. Methods: A non-randomised, controlled, before-after quasi-experimental trial was conducted in two intervention areas and one comparison area. The intervention built on a socioecological framework and took place across four settings: neighbourhoods, schools, workplaces and community health centres. Two independent cross-sectional surveys of adults aged 18–64 years at baseline and a subsequent follow-up were conducted in 2008/2009 and 2011 in the intervention and comparison areas. A 2-year intervention programme was begun in mid-2009 and continued until mid-2011. Results: A total of 2016 adults at baseline and 2016 adults at follow-up completed the survey. Over the 2-year intervention period, the intervention areas showed a statistically significant decline (25.2% vs 18.7%, p<0.001) in the prevalence of smoking compared with the comparison area (18.0% vs 16.4%, p=0.343). The proportion of individuals who had noticed anyone smoking in any of nine locations in the previous 30 days demonstrated a statistically significant decline in the intervention (78.9% vs 66.5%, p<0.001) and comparison (76.3% vs 66.5%, p<0.001) areas. The fruit and vegetable consumption score increased in a statistically significant manner in the intervention (24.84 vs 25.97, p=0.036) and comparison (24.25 vs 26.67, p<0.001) areas. The metabolic equivalent of physical activity increased from 1204 to 1386 (p=0.023) in the intervention areas compared with 918 to 924 in the comparison area (p=0.201). Conclusions: After a 2-year intervention, beneficial changes were noted in the intervention areas with respect to smoking and physical activity but not diet. A community-based multilevel intervention programme is feasible in urban China.